Rol del metabolismo de ácidos biliares en la sintomatología del síndrome de intestino irritable - Montenegro U., Cristián; Torres B., Claudio; Landskron R., Glauben; Hurtado H., Carmen; Gompertz J., Macarena (Revista Hospital Clínico Universidad de Chile, 2012)
Irritable Bowel Syndrome (IBS) is a multifactorial disease characterized by nonspecific symptoms such as abdominal pain and altered colonic transit, which may be present in other diseases such as inflammatory bowel disease and colorectal cancer, so that a differential diagnostic seems difficult. Although its origin is unknown, it is believed that psychological factors, genetic and physiological influence it. Among the hypotheses with greater force, is the exposure of the colon to bile acids by failure of regulatory mechanisms, mainly correlating with variant diarrheal IBS (IBS-D). This paper details the existing research to date attempting to find correlation between genetic variants of factors involved in the regulatory pathway of bile acids and IBS-D, particularly the study of single nucleotide polymorphisms in the gene Klotho beta.